Gender-transformative programming with men and boys to improve sexual and reproductive health and rights: a systematic review of intervention studies. Issue 10 (13th October 2020) - Ruane-McAteer, Eimear; Gillespie, Kathryn; Amin, Avni; Aventin, Áine; Robinson, Martin; Hanratty, Jennifer; Khosla, Rajat; Lohan, Maria
Abstract : Background: Global health organisations advocate gender-transformative programming (which challenges gender inequalities) with men and boys to improve sexual and reproductive health and rights (SRHR) for all. We systematically review evidence for this approach. Methods: We previously reported an evidence-and-gap map (http://srhr.org/masculinities/wbincome/ ) and systematic review of reviews of experimental intervention studies engaging men/boys in SRHR, identified through a Campbell Collaboration published protocol (https://doi.org/10.1002/CL2.203 ) without language restrictions between January 2007 and July 2018. Records for the current review of intervention studies were retrieved from those systematic reviews containing one or more gender-transformative intervention studies engaging men/boys. Data were extracted for intervention studies relating to each of the World Health Organization (WHO) SRHR outcomes. Promising programming characteristics, as well as underused strategies, were analysed with reference to the WHO definition of gender-transformative programming and an established behaviour change model, the COM-B model. Risk of bias was assessed using Cochrane Risk of Bias tools, RoB V.2.0 and Risk of Bias In Non-randomised Studies of Interventions . Findings: From 509 eligible records, we synthesised 68 studies comprising 36 randomised controlled trials, n=56 417 participants, and 32 quasi-experimental studies, n=25 554 participants. Promising programming characteristics include: multicomponent activities of education, persuasion, modelling and enablement; multilevel programming that mobilises wider communities; targeting both men and women; and programmes of longer duration than three months. Six of the seven interventions evaluated more than once show efficacy. However, we identified a significant risk of bias in the overall available evidence. Important gaps in evidence relate to safe abortion and SRHR during disease outbreaks. Conclusion: It is widely acknowledged by global organisations that the question is no longer whether to include boys and men in SRHR but how to do so in ways that promote gender equality and health for all and are scientifically rigorous. This paper provides an evidence base to take this agenda for programming and research forward.